Religion and American Politics from a Global Perspective - Froese, Paul (Religions, 2014)
Past findings and theory in the sociology of religion support two opposing perspectives concerning the influence of religion on American politics. Looking from within the United States, the commanding influence of religion on political rhetoric and voting patterns seems apparent. From a global perspective, the role that religion plays in American politics is less clear; in fact, one could argue that our political institutions are decidedly secular. I present support for both of these perspectives before turning to an international analysis of images of God using the Gallup World Poll. These data indicate the uniqueness of American religiosity and suggest that the ways in which religion affect politics in the United States is unusual for a post-industrial country. Namely, many Americans understand God as a political actor; because of this, American political culture mixes religious and political language with fervor, all while keeping church and state institutions separate.